CAUSES OF AND WAYS TO OVERCOME INTRAPERSONAL CONFLICTS - Голярдик, Наталія (SWorldJournal, 2024)
The article summarises the scientific and practical knowledge about the problem of intrapersonal conflicts. It is believed that it is internal problems that cause a number of certain feelings and a corresponding attitude towards oneself, as well as toward